2003
DOI: 10.1007/s11837-003-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Borosilicate glass and synroc R&D for radioactive waste immobilization: An international perspective

Abstract: Literature Review FeatureThis article provides a content analysis of publications on borosilicate glass and synroc, which are most widely used today for the immobilization of high-level radioactive wastes. Covering a period of 30 years, this study highlights the publication trends, the most productive countries, the language most frequently used, and the different categories of publications in these two subject areas. The research focuses on R&D efforts of different institutions and laboratories in these fi el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It can be seen in Fig. 7 that the normalized mass loss of Sr 2+ from samples S1S6 gradually decrease, which is Journal of the Ceramic Society of Japan 131 [6] 146-151 2023 JCS-Japan consistent with the intensities of the SrB 2 Si 2 O 8 peaks in Fig. 4.…”
Section: Pct Ion Leaching Text Analysissupporting
confidence: 76%
“…It can be seen in Fig. 7 that the normalized mass loss of Sr 2+ from samples S1S6 gradually decrease, which is Journal of the Ceramic Society of Japan 131 [6] 146-151 2023 JCS-Japan consistent with the intensities of the SrB 2 Si 2 O 8 peaks in Fig. 4.…”
Section: Pct Ion Leaching Text Analysissupporting
confidence: 76%
“…Because of high melting point, high thermal conductivity, radiation stability, ceramics are regarded as the second generation of HLW forms. Many results showed that ceramic forms have superior chemical durability to glass forms [4,5]. Ceramic incorporation of waste elements is based on the isomorphism of mineralogy.…”
Section: Introductionmentioning
confidence: 99%
“…Pb-Fe 3þ phosphates are generally studied due to their application as glasses in the nuclear waste industry (e.g., Reis et al, 2002;Oelkers & Montel, 2008). The family of phosphate glasses, which are based on pyrophosphate groups (P 2 O 7 ), are chemically stable in aqueous solutions and offer an excellent alternative to more conventional glasses such as sodium aluminophosphate glass (e.g., Polyakov et al, 1994) or borosilicate glass (e.g., Deokattey et al, 2003) for the immobilisation of nuclear waste (Karabulut et al, 2000).…”
Section: Introductionmentioning
confidence: 99%